Establishing biologically relevant sediment organic matter thresholds for estuaries and embayments of the Southern California Bight, USA. (October 2022) - Walker, Janet B.; Gillett, David J.; Sutula, Martha
Highlights: Thresholds for sediment TOC and TN were predictive of healthy, intact macrobenthic communities. Decline in macrobenthos condition with increasing gradients of sediment organic matter. Thresholds were consistent with other coastal ocean sites in Northern Hemisphere. First study to put forth sediment TN thresholds protective of benthic community condition. Thresholds could be used as a guideline in the management of eutrophication stressors. Abstract: Estuaries, lagoons, and embayments are key components of the coastal ecosystem and they are pervasively exposed to a variety of stressors – the most common of which is eutrophication. In shallow water coastal systems, eutrophication typically manifests as shifts in sediment oxygen horizons and accumulation of toxic reduced compounds in the porewater, which have direct, negative effects on the benthic fauna that live in these sediments. To catalog, prevent, and remediate these stressors, the coastal zone management community has expressed a need to identify targets for biostimulatory compounds and products in the environment that are protective of biological integrity of coastal waters. In response to this need, the present study identified and validated a series of sediment total organic carbon (TOC) and total nitrogen (TN) concentrations associated with changes in macrobenthic community composition across the estuaries and embayments of the Southern California Bight (SCB). Using data from a regional monitoring program, benthic community condition, quantified using the M-AMBI condition assessment index, was modelled as a function of TOC or TN concentration using logistic regression. Then, we evaluated eutrophication thresholds at concentrations corresponding to several relative probabilities (from 0.6 to 0.8), reflecting a range of policy makers' potential tolerance for risk of failing to meet biointegrity goals. Organic matter thresholds were extracted from the regressions that were predictive of healthy macrobenthic community condition at a 0.8 probability (1.23 mg g −1 TN, 15.51 mg g −1 TOC), 0.7 probability (2.58 mg g -1  TN, 22.9 mg g −1 TOC), or 0.6 probability (3.68 mg g −1 TN, 28.96 mg g −1 TOC) – as an illustration of how these types of stressor response models could be used to set targets for management of these ecosystems. These thresholds were subsequently validated by applying them to data held back from the model creation and by comparing them to taxon-specific inflection points identified from TITAN changepoint analysis of the macrobenthic/TOC/TN calibration data. The different TOC and TN thresholds correctly classified between 67 and 86% of the validation samples, with most of the misclassifications being instances of low organic matter concentration but poor community condition (i.e., false positives). The TOC thresholds identified from our Southern California dataset fell within a similar range (10–35 mg g −1 ) that has been linked to benthic community impacts from a variety of coastal ocean sites across the Northern Hemisphere. The consistency in thresholds across multiple habitats and different types of biota is suggestive of a general, quantitative threshold for organic matter accumulation in near shore sediment habitats and could be useful for informing the management of coastal ecosystems and setting targets biostimulatory stressors in these systems.